Analysis of Competitiveness and Added Value of Red Chili Supply Chain in Traditional and Modern Markets - Zalukhu, Penari (Jurnal Teknologi dan Ilmu Pertanian, 2025)
Red chili is a strategic horticultural commodity with high price fluctuations and a complex supply chain. The shift of some consumption to modern retail has changed the market structure, the incentives of actors, and the formation of added value along the chain. This study analyzes: (1) product flow maps, information, and costs in two types of channels—traditional and modern markets; (2) competitiveness at the farm and downstream levels; (3) the formation of added value and its distribution among actors; and (4) the determinants of efficiency and price stability. The study design is comparative–cross-channel with surveys of farmers, collectors, wholesalers, and retailers (n≈120–200 respondents) supplemented by focus group discussions. Supply chain mapping was conducted using a value chain mapping approach. Competitiveness was measured using the Policy Analysis Matrix (PAM) at the farm level and margin–farmer’s share analysis and price transmission elasticity for downstream. Value added at each node was calculated using the Hayami method, while the influence of managerial practices (quality standards, contracts, cold chain, price information) on efficiency was analyzed using SEM-PLS. The results show differences in the structure and behavior of actors between the two channels. Modern markets tend to demand quality and cold chain standards that reduce losses and increase net value added at the sorting-packaging node, while traditional markets have higher marketing margins but a relatively lower farmer share. Price transmission from downstream to upstream is proven to be faster in modern channels. Standardization practices, partnerships, and the use of cold chains have a positive and significant impact on cost efficiency. Strengthening upstream-downstream partnerships, adopting quality standards, and investing in cold chains can increase competitiveness and improve the distribution of added value to farmers. Logistics facilitation policies and real-time price information are recommended to reduce volatility. This study combines PAM, Hayami, and simultaneous cross-channel price transmission analysis for chilies, providing comparative evidence for formulating targeted interventions.